2015
DOI: 10.3892/br.2015.450
|View full text |Cite
|
Sign up to set email alerts
|

p38 mitogen-activated protein kinase inhibits USP22 transcription in HeLa cells

Abstract: Abstract. Elevated expression of ubiquitin-specific processing enzyme 22 (USP22) was identified in multiple types of human cancers, and was correlated with tumorigenesis and progression. Despite an increase in the numbers of studies in the physiological function of USP22, little is known regarding the regulation of its expression. The 5' flanking sequence of the USP22 gene was recently characterized. In the present study, USP22 transcription was regulated by p38 mitogen-activated protein kinase (MAPK). Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Our previous study revealed that transcription factors SP1 and CREB-1 bound to the USP22 promoter and regulated the expression of USP22 (18). In addition, certain chemotherapeutic drugs, including cisplatin and TSA, downregulate the expression of USP22 and trigger apoptosis in HeLa cells (19,20). In the current study, treatment with THP decreased the expression of USP22 in HeLa cells in a dose-and time-dependent manner.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Our previous study revealed that transcription factors SP1 and CREB-1 bound to the USP22 promoter and regulated the expression of USP22 (18). In addition, certain chemotherapeutic drugs, including cisplatin and TSA, downregulate the expression of USP22 and trigger apoptosis in HeLa cells (19,20). In the current study, treatment with THP decreased the expression of USP22 in HeLa cells in a dose-and time-dependent manner.…”
Section: Discussionsupporting
confidence: 58%
“…Transfection and dual luciferase assays. The USP22 promoter and its mutant constructs were generated as previously described (18,19). HeLa cells were cultured in 24-well plates and transfected with 0.8 µg pGL3-basic construct, P-2828 (-2828/+52), P-595 (-595/+52), or P-210 (-21/+52) promoter regions together with 0.2 µg pRL-TK (Promega Corporation, Madison, WI, USA) using Lipofectamine ® 2000 (Invitrogen; Thermo Fisher Scientific, Inc.), according to the manufacturer's protocol.…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, recent studies show that USP22 deubiquitinase activity can raise protein levels of Sirt1 by reversing this ubiquitination [ 92 , 93 , 94 , 95 ]. The proximal promoter of the USP22 gene contains an Sp1-binding site, and Sp1 binding suppresses the gene’s transcription [ 96 , 97 ]. Activated p38 MAP kinase can confer a phosphorylation on Sp1 that expedites its binding to its response elements and has been found to inhibit Sp1 expression at the transcriptional level [ 97 , 98 ].…”
Section: Controlling Beta Cell Oxidant Stress—focus On Nox2 Mitophagy and Mitochondrial Biogenesismentioning
confidence: 99%